Event-Triggered Control for Multiagent Systems with the Problem of Packet Losses and Communication Delays When Using the Second-Order Neighbors’ Information - Chuan Yan; Mei Yu; Guangming Xie; Yu Liu (Abstract and Applied Analysis)
This paper mainly investigates the event-triggered control for discrete-time multiagent systems with the problem of packet losses and communication delays when both the first-order and the second-order neighbors’ information are used. Event-triggered control laws are adopted so as to reduce the frequency of individual actuation updating under the sampled-data framework for discrete-time agent dynamics. The communication graph is undirected and the loss of data across each communication link occurs at certain probability, which is governed by a Bernoulli process. It is found that the distributed consensus speeds up by using the second-order neighbors’ information when packet losses and communication delays occur. Numerical examples are given to demonstrate the effectiveness of the proposed methods.